2012
DOI: 10.1111/j.1600-048x.2012.05640.x
|View full text |Cite
|
Sign up to set email alerts
|

Black‐capped chickadees Poecile atricapillus sing at higher pitches with elevated anthropogenic noise, but not with decreasing canopy cover

Abstract: Several songbird species sing at higher frequencies (i.e. higher pitch) when anthropogenic noise levels are elevated. Such frequency shifting is thought to be an adaptation to prevent masking of bird song by anthropogenic noise. However, no study of this phenomenon has examined how vegetative differences between noisy and quiet sites influence frequency shifting. Variation in vegetative structure is important because the acoustic adaptation hypothesis predicts that birds in more open areas should also sing at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 67 publications
(86 reference statements)
4
23
0
Order By: Relevance
“…Transmission experiments show that urban noise overlaps black-capped chickadee songs and has the potential to significantly reduce signal-to-noise ratios [29]. Further, observational and experimental exposure studies show that black-capped chickadees exhibit spectral plasticity in response to anthropogenic noise [30,31] and spectrally shift their songs away from narrow bands of overlapping noise [32]. However, we do not know whether this ability to avoid masking needs to be learned or whether the tendency to shift upwards in response to lowfrequency noise is dependent upon prior experience with signalling under noisy conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Transmission experiments show that urban noise overlaps black-capped chickadee songs and has the potential to significantly reduce signal-to-noise ratios [29]. Further, observational and experimental exposure studies show that black-capped chickadees exhibit spectral plasticity in response to anthropogenic noise [30,31] and spectrally shift their songs away from narrow bands of overlapping noise [32]. However, we do not know whether this ability to avoid masking needs to be learned or whether the tendency to shift upwards in response to lowfrequency noise is dependent upon prior experience with signalling under noisy conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, singing louder may be an effective way of increasing the range of vocalizations in noisy conditions and singing higher may allow birds to sing louder (Nemeth et al, 2013). Other studies have also found that black-capped chickadees do sing higher frequency songs in noisy habitats (Proppe et al, 2012), and will shift songs in response to experimental overlapping noise (Goodwin & Podos, 2013), but spectral flexibility has not been observed in mountain chickadees. This potential spectral constraints on mountain chickadee song may result in this species experiencing greater difficulties communicating in urban green-spaces compared to black-capped chickadees.…”
Section: Signal Masking and Masking Avoidancementioning
confidence: 97%
“…Dowling et al (2012) found opposing effects of urban noise and urban habitat structure, with low frequencies being affected by noise, and high frequencies by habitat structure. Furthermore, a recent analysis examined correlations between song variation in black-capped chickadees and both ambient noise interference and habitat structure (Proppe et al, 2012). They found that variation in overall song frequency correlated with ambient noise levels, but not with habitat structure, while internal frequency ratios within songs showed habitat-dependent variation.…”
Section: Thesis Goalsmentioning
confidence: 99%
“…50-2000 km; Brewer et al, 2006), so birds may encounter individuals originating from different geographical regions. Chickadees from different habitat types (high-and low-quality habitat; Grava et al, 2012) or habitats with different levels of anthropogenic noise (Proppe et al, 2012) produce songs with acoustic differences. In addition, the habitat of origin of both the singer and the song receiver influence how the singer is perceived (Grava et al, 2013).…”
Section: Perceptual Categorizationmentioning
confidence: 99%